Perancangan Sistem Informasi Perlombaan Berbasis Website untuk Kemudahan Penyampaian Informasi dan Pendaftaran Lomba - Ahmad Fajar Maulana; Atang Susila (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Information technology and science are developing so fast. Therefore many people are competing to improve their abilities and achievements. Not only competing against others but also competing against oneself to improve the achievements that have been achieved previously. Competition can of course also be a factor for the progress of a region. Where a competition is a medium to show each other the interests and talents of the participants for their own good and the good of an area. However, competitions are often lacking in the number of participants and the participant registration process is often considered by the public due to distance issues and transportation costs. Therefore, the development of a website-based race information system was created with the aim of making it easier for the organizers to convey information about the competition and making it easier for the public in the participant registration process. System development using the waterfall method by analyzing, designing, implementing and testing. In the final stage of system development, testing of the processes that occur in the race information system is carried out. The things that have been done and what have not been done in the development of this system will be described at the end of this journal.